Electromagnetic field in Lyra manifold: a first order approach - Casana, R. [UNESP]; Melo, C. A. M. de [UNESP]; Pimentel, B. M. [UNESP] (Sociedade Brasileira de Física, 2005)
We discuss the coupling of the electromagnetic field with a curved and torsioned Lyra manifold using the Duffin-Kemmer-Petiau theory. We will show how to obtain the equations of motion and energy-momentum and spin density tensors by means of the Schwinger Variational Principle.